Outcomes of a National, Cross-Sector Antimicrobial Stewardship Training Initiative for Pharmacists in England - Vincent Ng; Diane Ashiru-Oredope; Helena Rosado; Beth Ward (MDPI AG, 2021)
(1) Background: Pharmacists play a pivotal role in tackling Antimicrobial resistance through antimicrobial stewardship (AMS) and are well placed to lead behaviour change interventions across the healthcare system; (2) Methods: A cross-sector AMS training initiative for pharmacists was implemented across England, with three cohorts between 2019-2021. Each cohort took part in an introductory workshop, followed- by a workplace-based quality improvement project supported by peer-assisted learning sessions. Completion of training was determined by an end of training assessment after three to four months. Outcome data and learner survey results were collated, anonymised, and analysed by the training provider. (3) Results: In total, 118 pharmacists participated in the introductory workshop, 70% of these subsequently undertook an improvement project, and 48% engaged workplace stakeholders in the process. Interventions were designed by 57% of learners and 18% completed a at least one Plan-Do-Study-Act cycle. Approximately a quarter of learners met the requirements for a Certificate of Completion. Knowledge quiz scores were obtained from 115 learners pre-training and 28 learners post-training. Paired t-tests conducted for 28 learners showed a statistically significant improvement in mean score from 67.7% to 81.1% (p < 0.0001). Sixty-two learner survey responses were received during the training and 21 follow-up survey responses 6 to 12 months post training. Of the 21 responses to the follow-up survey, ongoing quality improvement work and improvement outcomes were reported by nine and six learners, respectively. (4) Conclusions: The delivery of workplace-based training at scale can be challenging, however this study demonstrates that coupling learning with workplace implementation and peer support can promote behaviour change in learners. Further study into the impact of providing pharmacists across sectors and geographies with access to this type of training will help inform ongoing workforce development interventions.